Blood lactate level responses and comparison with submaximal running and roller skiing in cross-country skiers - Cetin, E.; Bilgin, U.; Schurmann, B. C.; Yarim, I.; Dolek, B. E, (Collegium Antropologicum, 2013)
The purpose of this study is to examine the effect of 30-minute duration submaximal running and roller skiing exercises, which are among the most important aerobic exercise models in cross-country skiers, on lactic acid levels. The study group comprised 6 female and 4 male athletes (age: 16.87±1.87years, body height: 168.35±5.66 cm, body weight: 56.83±7.1kg) who competed in cross-country skiing at national and international level. All athletes participated in the study voluntarily. Measurements were performed three times as basal (1st measurement), immediately after exercise (2nd measurement) and 5 minutes after finishing exercise (3rd measurement).Statistical analysis was conducted using SPSS (version 11.5). A significant increase (P<0.01) in lactic acid levels was found for both 30-minute submaximal exercise types; however, this effect did not differ statistically between groups. Running exercises caused greater fatigue than skiing exercises, according to percentage values, but the difference in fatigue levels between exercise types was not statistically significant.